ANALYSIS OF NOTIFIED CASES OF VIOLENCE AGAINST WOMEN - Paulo Roberto Mattos; Ivoney Silva Ribeiro; Vania Carla Camargo (Universidade Federal do Paraná, 2012)
Violence is one of the principal causes of morbidity and mortality in the world and is considered a public health problem. This documental research evaluated epidemiological, clinical and sociodemographic aspects of women who were victims of violence in 200 notified cases in March and April 2010 in the municipality of Pinhais in Paraná. The results show that the majority of the cases of aggression were caused by the woman's own partner, against women who were young and with a low level of education; the most frequent duration of the subjection to the situation of violence varied between three and four years. Aggression occurred most frequently in two neighborhoods of the municipality, and in the victim's home, being characterized by physical and psychological aggression; the use of physical force was most common, with limbs and head being most affect by the actions. The majority of the victims did not express an opinion about the desire or not for reconciliation with the aggressor. The analysis permitted the characterization of violence against women in the municipality.